Effect of living close to a main road on asthma, allergy, lung function and chronic obstructive pulmonary disease. Issue 10 (21st September 2009) - Pujades-Rodríguez, M; Lewis, S; Mckeever, T; Britton, J; Venn, A
Abstract : Background: A number of epidemiological studies suggest that the risk of asthma is increased among those living in close proximity to major roads. However, the evidence is inconsistent, and effects on asthma and related respiratory and allergic conditions using objective measures such as lung function and allergic sensitisation have not been widely investigated. Methods: In 1995, 1996 and 2001 data on respiratory and allergic disease, along with demographic and lifestyle factors, were collected in 59 285 children (aged 2–16 years) and adults as part of the Health Survey for England, a nationally representative annual survey. Using Geographical Information System software, we mapped the location of each participant's home and computed distance to the nearest major road. We estimated the effect of distance on self-reported wheezing in the past year, asthma, eczema and hay fever in 50 994 participants, and on 1-second forced expiratory volume (FEV1 ), immunoglobulin E and spirometry-defined chronic obstructive pulmonary disease (COPD) in subgroups of those aged 7+, 11+ and 16+ years, respectively. Results: Living within 150 m from a major road was not significantly associated with an increased risk of any of the outcome variables in any age group (adjusted odds ratios ranged from 0.85 to 1.05). Furthermore there was little evidence that risk increased with increasing proximity across the 0–150 m range where contrasts in traffic-related pollutant concentrations are greatest. Conclusion: Our analysis of a large and nationally representative population sample did not provide evidence of an adverse effect of living in close proximity to main roads on the risk of asthma, COPD or allergic disease in England.